Revitalisasi Peran UIN Sumut Melalui KKN Mewujudkan Masyarakat Bermartabat di Desa Kuta Ujung - Watni Marpaung; Jainul Husni; Satria Akbar Desky; Iqbal Pratama; Riki Pranata (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
North Sumatra UIN students are demanded to revitalize in order to create a dignified society. Revitalization is an effort to re-vitalize an area or part of a city that was once vital/lived, but then suffered a setback/degradation. So in creating this, UIN North Sumatra students create a work program that guides creating a dignified society, as follows: 1) Overcoming Stunting Problems in Village Communities from House to House to create a Stunting Free Society; 2) Creating a society and not illiterate and illiterate Al-Qur'an; 3) Accompanying legal problems in the village; 4) Provide educational learning education to community cadres in order to create a dignified and integrity society; 5) Provide Islamic insight in the fields of creed, sharia and Sufism; 6) Help build a creative economic community; 7) Accompanying the community's social problems; 8) Engage and assist community agriculture and create a society that is not technologically illiterate; 9) Hold kulibas (a fifteen minute lecture) after maghrib in order to increase religious insight. Keywords : Revitalization, Dignity, Overcoming.